2010
DOI: 10.1007/s10457-010-9316-9
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic use of plants by local communities in and around Rema-Kalenga Wildlife Sanctuary: implications for protected area management in Bangladesh

Abstract: Traditional systems of medicine have become a topic of global importance recently. Increased commercialization of economically important medicinal plants has resulted in overharvesting and threatening their survival. The present study was carried out to document the indigenous uses of medicinal plants by the local communities in and around Rema-Kalenga Wildlife Sanctuary, Bangladesh. Data collection was predominantly qualitative recording the species use, identifying their relative importance (RI) and assessin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…plants, trees were the most frequent growth form (37.78%), followed by herbs (24.44%), shrubs (22.22%), vine (8.89%), and palms (6.67%). A similar trend was also observed that trees were the most used growth form of medicinal plants in Bangladesh [2,9,[31][32][33][34][35][36], but with a few exceptions [12,37] where they found that herbs were mainly used as medicinal plants.…”
Section: Medicinal Plants Species Compositionsupporting
confidence: 64%
“…plants, trees were the most frequent growth form (37.78%), followed by herbs (24.44%), shrubs (22.22%), vine (8.89%), and palms (6.67%). A similar trend was also observed that trees were the most used growth form of medicinal plants in Bangladesh [2,9,[31][32][33][34][35][36], but with a few exceptions [12,37] where they found that herbs were mainly used as medicinal plants.…”
Section: Medicinal Plants Species Compositionsupporting
confidence: 64%
“…In Bangladesh's protected areas, many aspects of forest resource utilization have been identified as responsible for their degradation (Chowdhury & Koike, 2010a), posing serious threats to the biological diversity. Of the 10 threats identified in this study, five (illegal tree cutting, harvesting NTFPs, forestland grabbing for real estate business, wildlife poaching, and environmentally non-friendly tourism) were directly or indirectly related to resource utilization.…”
Section: Discussionmentioning
confidence: 99%
“…How NWFPs support livelihood is not yet known because the factors and the extent to which people depend on the forest are not yet understood (Lawrence et al 2005). The commercialization of medicinal plants, which could be a source of income, may lead to over-harvesting (Chowdhury and Koike 2010, Kala et al 2004, Kala 2005, Hersch-Martínez 1995, van Andel and Havinga 2008, Vodouhe et al 2008. There is growing concern about biodiversity and loss of medicinal plant species, of which 8% are under threat worldwide (Walter and Gillett, 1998).…”
Section: Introductionmentioning
confidence: 99%